2010
DOI: 10.1161/circheartfailure.110.938506
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Myocarditis Due to H1N1 Influenza

Abstract: W e report 2 cases of fulminant myocarditis caused by the H1N1 strain of influenza. As the incidence of H1N1 influenza infection continues to rise, physicians should be aware of this rare and potentially fatal complication because early diagnosis and aggressive supportive measures are imperative. Case 1A 52-year-old woman presented with a 3-day history of chest pain, dyspnea, diffuse myalgias, and fever. The ECG demonstrated low voltage with diffuse ST segment elevation ( Figure 1). The troponin I was 5 ng/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The purpose for using ECMO in this particular case was circulatory/hemodynamic support. Al-Amoodi et al 7 and Bratincsak et al 8 have reported limited experiences in the use of ECMO in H1N1 infection with fulminant myocarditis. In our case, we implemented ECMO at a very early stage, resulting in a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose for using ECMO in this particular case was circulatory/hemodynamic support. Al-Amoodi et al 7 and Bratincsak et al 8 have reported limited experiences in the use of ECMO in H1N1 infection with fulminant myocarditis. In our case, we implemented ECMO at a very early stage, resulting in a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown elevation of cardiac injury markers and acute phase proteins are indicators of cardiovascular events associated with influenza virus infection (38,39). Myocardial injury can be determined by serum biomarkers including the MB form of creatine kinase (CK-MB), lactate dehydrogenase (LDH), and troponin (TnT) (40,41).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
“…Acute myocarditis associated with other avian flu, H1N1 in particular, has been widely reported and is potentially lethal in form as fulminant myocarditis . However, a national survey in Japan on myocarditis‐associated 2009 H1N1 pandemic only revealed 15 myocarditis cases in a total of 24203 patients .…”
Section: Discussionmentioning
confidence: 99%
“…1. The number of patients in each group is as follows: Group I (0), Group II (21), Group III (15) and Group IV (4). All patients have been tested H7N9 negative as on 9 May 2013, among whom eighteen have been discharged from hospital, five transferred to general ward and five died.…”
Section: Patient Characteristicsmentioning
confidence: 99%